Militarization, Multiculturalism and Mythology: Canadian National Identity in a New Age of Empire - McCready, L. (My University, 2012)
This dissertation maps the militarization of Canadian culture under the War on Terror. The first section examines the rise of everyday life militarizing cultural practices such as the Yellow Ribbon campaign to Support the Troops, Red Fridays, and the Highway of Heroes. The second section takes up militarizing cultural texts: the most recent wave of Canadian Forces recruiting advertisements, the CBC radio play Afghanada, and Paul Gross’s 2008 film Passchendaele. Across these diverse sites of analysis I argue that it is precisely through the mobilization of the previous national myths of multiculturalism, peacekeeping and tolerance that the contrary cultural politics of the new militarism coheres.
Keywords: Militarization; national identity; support our troops; cultural politics; public discourse; Canada; Other English Language and Literature; Other English Language and Literature